Multimodal analgesia with multiple intermittent doses of erector spinae plane block through a catheter after total mastectomy: a retrospective observational study - Hong, Boohwi (Korean J Pain, 2019)
BACKGROUND: Although case reports have suggested that the erector spinae plane block (ESPB) may help analgesia for patients after breast surgery, no study to date has assessed its effectiveness. This retrospective observational study analyzed the analgesic effects of the ESPB after total mastectomy. METHODS: Forty-eight patients were divided into an ESPB group (n = 20) and a control group (n = 28). Twenty patients in the control group were selected by their propensity score matching the twenty patients in the ESPB group. Patients in the ESPB group were injected with 30 mL 0.375% ropivacaine, followed by catheter insertion for further injections of local anesthetics every 12 hours. Primarily, total fentanyl consumption was compared between the two groups during the first 24 hours postoperatively. Secondary outcomes included pain intensity levels (visual analogue scale) and incidence of postoperative nausea and vomiting (PONV). RESULTS: Median cumulative fentanyl consumption during the first 24 hours was significantly lower in the ESPB (33.0 μg; interquartile range [IQR], 27.0–69.5 μg) than in the control group (92.8 μg; IQR, 40.0–155.0 μg) (P = 0.004). Pain level in the early postoperative stage (<3 hr) and incidence of PONV (0% vs. 55%) were also significantly lower in the ESPB group compared to the control (P = 0.001). CONCLUSIONS: Intermittent ESPB after total mastectomy reduces fentanyl consumption and early postoperative pain. ESPB is a good option for multimodal analgesia after breast surgery.